2013
DOI: 10.1002/jmri.24304
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of benign and malignant distal biliary strictures: Value of adding diffusion-weighted imaging to conventional magnetic resonance cholangiopancreatography

Abstract: The addition of DWI to MRCP significantly improved diagnostic accuracy in the characterization of distal biliary strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Unenhanced T2- and T1-weighted images were obtained with the Half Fourier Single-shot Turbo Spin Echo sequence (HASTE) and the dual echo in- and opposed-phase Fast Low Angle Shot (FLASH) sequence techniques, respectively. MR cholangiography using 3 MR methods followed: 1) breath-hold single-section rapid acquisition with Turbo Spin Echo (TSE), 2) breath hold multi-section HASTE, and 3) respiratory-triggered multisection three-dimensional (3D) TSE ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Unenhanced T2- and T1-weighted images were obtained with the Half Fourier Single-shot Turbo Spin Echo sequence (HASTE) and the dual echo in- and opposed-phase Fast Low Angle Shot (FLASH) sequence techniques, respectively. MR cholangiography using 3 MR methods followed: 1) breath-hold single-section rapid acquisition with Turbo Spin Echo (TSE), 2) breath hold multi-section HASTE, and 3) respiratory-triggered multisection three-dimensional (3D) TSE ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although periductal infiltrating type CC can show skipped lesions, it is more frequently observed in benign sclerosing cholangitis such as IgG4-related sclerosing cholangitis (156,159). DWI can show diffusion restriction in malignant strictures and it would provide additional value for differentiating malignant from benign strictures in extrahepatic CC (160,161). However, the added value of DWI for perihilar CC remains controversial compared with dynamic T1-weighted imaging (162,163).…”
Section: Benign Versus Malignant Biliary Stricturesmentioning
confidence: 99%
“…Therefore, the diagnostic value of a combined MRCP and dynamic study with or without DWI was not investigated; however, in an earlier study by Yoo et al, their results revealed that both the sensitivity and specificity of combined MRCP and DWI did not significantly differ from that of MRCP, DWI, and contrast-enhanced T1WI combined [18].…”
Section: Discussionmentioning
confidence: 97%
“…Although combining MRCP and contrast-enhanced MRI or EUS may facilitate the differential diagnosis of biliary strictures, the benefit of using contrast may not outweigh its risk for the development of nephrogenic systemic fibrosis in patients with poor renal function, and the routine use of EUS may also increase the medical costs and complexity of the diagnostic workup [18].…”
Section: Discussionmentioning
confidence: 99%